Influence of a local laser heat treatment on the bending properties of aluminium extrusion profiles - Graser, Matthias; Pflaum, Nico; Merklein, Marion (Procedia CIRP, 2018)
Driven by ecological and economical demands, lightweight design and in this context, the substitution of steel by aluminium has become a major trend in the automotive industry. However, design possibilities are limited by the low formability of aluminium alloys. One approach to overcome these limitations is the usage of tailor heat treated semi-finished products. By a local short-term heat treatment, distinct areas are softened, which can be used to improve the material flow into critical forming zones. Within this work, the influence of local short-term heat treatment on the formability of aluminium extrusion profiles is analysed by experimental bending tests. Aims are the enhancement of maximum reachable bending angles as well as the reduction of cross section deformations. Therefore, different heat treatment layouts are applied by laser irradiation. Finally, the bending results are evaluated and promising heat treatment strategies are derived.
LFT Import::2019-07-29 (2336)
Keywords: Aluminium; Bending; Extrusion profiles; Heat treatment